Strategies to Enhance Learning Motivation Through Social and Academic Interaction Among English Education Students at the University of Mataram - Kusuma, Wien Bani; Santos, Maria Lourdes (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study investigates strategies to enhance learning motivation through social and academic interaction among English Education students at the University of Mataram. Learning motivation plays a central role in shaping academic engagement, persistence, and language achievement in higher education contexts. Previous research emphasizes that motivation is influenced not only by internal psychological factors but also by interactional dynamics within academic environments. However, limited empirical studies have examined the combined influence of social and academic interaction within Indonesian English Education programs. This research applies a quantitative explanatory design using Partial Least Squares Structural Equation Modeling. A total of 247 undergraduate students participated through proportional stratified random sampling. Data were collected using validated Likert scale questionnaires measuring social interaction, academic interaction, and learning motivation. Reliability and validity were confirmed through Cronbach’s alpha, composite reliability, Average Variance Extracted, and discriminant validity testing. Structural model evaluation was conducted using bootstrapping procedures to test hypothesis significance. The findings reveal that both social interaction and academic interaction significantly influence learning motivation. Social interaction positively predicts motivation, indicating that peer collaboration, emotional support, and classroom belonging strengthen students’ intrinsic engagement. Academic interaction demonstrates a stronger predictive effect, showing that lecturer feedback, dialogic teaching, and structured academic communication enhance students’ competence perception and motivational commitment. The structural model explains 58 percent of the variance in learning motivation, indicating substantial explanatory power. These results confirm that learning motivation is strongly shaped by interaction based factors rather than individual traits alone. The study provides empirical support for implementing structured peer collaboration and interactive instructional strategies to strengthen motivational outcomes in English Education programs. The findings offer practical implications for curriculum design and instructional practice aimed at sustaining student engagement and improving language learning performance in higher education contexts.